Python web frameworks - Guardia, Carlos de la (O'Reilly Media, 2016)
Even though JavaScript tools dominate today's web development landscape, Python provides aspiring web developers with a wide variety of useful web frameworks, written in a powerful, easy-to-learn language. This O'Reilly report surveys 30 Python web frameworks that have more than 1,000 monthly downloads and provides a deeper look into six of the most widely used. Longtime Pythonista Carlos de la Guardia describes Python web frameworks ranging from full-stack options that offer a lot of functionality to micro frameworks that focus on simplicity with fewer features. You'll not only get pointers on how to choose a framework that best fits your development needs, but you'll also learn what it takes to create your own. Take a tour of Python frameworks, from Appier, Cyclone, and Fantastico to Grok, Muffin, and Twisted Dive into details on the top six Python frameworks--Django, Flask, Tornado, Bottle, Pyramid, and CherryPy Review code examples, testing capabilities, best uses, and ways to get started with each of the top six Learn Python's building blocks for creating your own framework, and explore why you'd want to pursue this option.